Ubuntu and Business Ethics: Problems, Perspectives and Prospects - West, Andrew (2014)
The African philosophy of Ubuntu is typically characterised as a communitarian philosophy that emphasises virtues such as compassion, tolerance and harmony. In recent years there has been growing interest in this philosophy, and in how it can be applied to a variety of disciplines and issues. Several authors have provided useful introductions of Ubuntu in the field of business ethics and suggested theoretical ways in which it could be applied. The purpose of this paper is to extend this discussion by providing a more critical analysis of Ubuntu and business ethics with the aim of clarifying the role that Ubuntu can play, and providing guidance for further research in this area. The analysis consists of three sections. In the first, certain problems are identified within the existing literature. This is followed by a consideration of alternative perspectives and interpretations of Ubuntu. The last section, following from the first two, identifies specific areas requiring further research, both empirical and non-empirical, as well as ways in which Ubuntu could be fruitfully applied.
Keywords: Africa; African Philosophy; South Africa; Ubuntu